2015
DOI: 10.3346/jkms.2015.30.7.860
|View full text |Cite
|
Sign up to set email alerts
|

APOEPolymorphism Is Associated with C-reactive Protein Levels but Not with White Blood Cell Count: Dong-gu Study and Namwon Study

Abstract: We evaluated the association of the APOE polymorphism with serum C-reactive protein levels and white blood cell count in two large population-based studies in Korean. The datasets included the Dong-gu study (n = 8,893) and the Namwon Study (n = 10,032). APOE genotypes were identified by polymerase chain reaction-restriction fragment length polymorphism. Multivariable linear regression analysis was performed to evaluate the relationship of APOE genotypes with C-reactive protein levels and white blood cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…Greater Metabolic_risk (derived from body mass index, serum insulin and plasma triglyceride levels) was associated with higher serum CRP levels (β = 0.20 ± 0.076, p = 0.009). However, greater AD risk conferred by APOE genotype was associated with lower peripheral CRP (β = −0.17 ± 0.064, p = 0.019), consistent with previous reports (Yun et al, 2015). Metabolic risk did not have a significant direct effect on Brain_structure .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Greater Metabolic_risk (derived from body mass index, serum insulin and plasma triglyceride levels) was associated with higher serum CRP levels (β = 0.20 ± 0.076, p = 0.009). However, greater AD risk conferred by APOE genotype was associated with lower peripheral CRP (β = −0.17 ± 0.064, p = 0.019), consistent with previous reports (Yun et al, 2015). Metabolic risk did not have a significant direct effect on Brain_structure .…”
Section: Resultssupporting
confidence: 91%
“…APOE 4 has been associated previously with thinner cortex in older adults (Fan et al, 2010; Liu et al, 2010). A lower blood CRP level in APOE 4 carriers is also consistent with previous studies in humans (Hubacek et al, 2010; Yun et al, 2015). However, it is currently unclear what is mechanistically driving this relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, Bailey and colleagues [68] found that APOE ɛ4 carriers had smaller medial temporal lobe volumes and that the volume mediated the relationship between memory performance and APOE genotype. APOE ɛ4 is also associated with altered levels of C-reactive protein, a systemic marker of inflammation [69] which has been found to be associated with frailty, [70] memory performance and lower medial temporal volume [71], and cognitive decline in a non-demented population [72]. Taken together, frailty biomarkers, APOE , and age-related memory decline may share common pathophysiological mechanisms (i.e., brain atrophy, beta-amyloid burden, inflammatory markers) [73].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, this is not the case, at least with CRP. Studies have consistently shown that CRP levels are lower in APOEε4 carriers ( Ukkola et al, 2009 ; Lima et al, 2014 ; Metti et al, 2014 ; Yun et al, 2015 ). Marz et al (2004) proposed that the metabolism of CRP might be associated with the mevalonate/cholesterol synthetic pathway, which might be downregulated in APOEε4 carriers.…”
Section: Apoeε4 Inflammation and Alzheimer’s Diseasementioning
confidence: 99%